Wildlife Economics : Case Studies from Ghana, Kenya, Namibia, and Zimbabwe - Bojo, Jan (World Bank, Washington, DC, 2012)
Between 1970 and 1992, the World Bank assisted financially in about 15 wildlife-related projects in Sub-Saharan Africa. The lending volume was US$ 368 million or about 1percent of the Bank's totals lending during the same period. While geographically, these projects have been concentrated in East Africa, especially Kenya, the others are located in Somali, Malawi, Botswana, Cote d'Ivoire, Zimbabwe, Ghana, the Central African Republic, Burkina Faso, and Mali. The case studies focus on four major themes: (i) the financial and economic viability of wildlife; (ii) the significance of wildlife as meat or 'bush meat'; (iii) policy implications; and (iv) environmental impact. Evidence in this last area, however, remains qualitative and anecdotal. A critical hypothesis of this study is that the property rights structure is a key factor in determining the choice between wildlife and livestock utilization.